KAJIAN KEBUTUHAN WISATAWAN DIFABEL DALAM BERWISATA (STUDI KASUS MUSEUM BENTENG VREDEBURG) - Kusumaningrum, Haritsah (Kepariwisataan: Jurnal Ilmiah, 2018)
Tourism is known as a borderless sector or has no separating boundaries. It is important to facilitate accessibility for tourist with disability, so the development of a destination will increase as it can be enjoyed by anyone. The research was conducted using qualitative descriptive method. Data were collected through observation and in-depth interviews. Then the data are analyzed by qualitative descriptive technique include: data reduction, data presentation and conclusion. The results revealed that the needs of tourists with visual impairment include: guide tiles, tacticle map, signs, showroom lighting, audio availability, Braille text and hands on. The needs of tourist with mobility impairment include: accessibility in parking areas, ramps, doors, toilets, pathways, signs, plenty of seats, enough space in exhibit room, and displays are in suitable height. Keywords: accessibility, disabled, accessible tourism, museum